Gant Development S.A.: The effectiveness of bankruptcy prediction models in case of sudden bankruptcy. Case study - Ulyana Dzyuma-Zaremba (e-Finanse: Financial Internet Quarterly, 2015)
Company bankruptcies are an inseparable element of market economy. We may observe the tendency to view bankruptcy as a problem of weak and usually small entities facing problems when trying to meet the challenge posed by strong competition. Big companies, however, also fall, and their bankruptcy cannot be predicted by even the most experienced analysts. The aim of the article is to examine the effectiveness of the bankruptcy prediction models in case of sudden bankruptcies,on the example of Gant Development S.A. The author attempts to classify the real estate developer's bankruptcy as "staged" bankruptcy by performing an analysis of company activities in the period of 2010-2013. The study was conducted using Polish models of linear discriminant analysis, widely popular in the Polish literature as well as the models which reflect the branch specificity of the examined entity.
Keywords: G33; M21; C53; 330; bankrupcy prediction; discriminant analysis; planned abnkrupcy; financial distress